Formulasi Mie Substitusi Tepung Kelapa untuk Meningkatkan Kadar Serat - Nuraini, Sekarsari; Wirjatmadi, Bambang (Media Gizi Kesmas, 2024)
Background: Non-communicable diseases can be prevented with dietary modifications, but major dietary changes are difficult for most people. One alternative that can be done is to add important nutrients in the form of a familiar diet menu, such as noodles. One of the nutrients that can help is fiber. One of the sources of fiber in Indonesia is coconut flour, which is a by-product of coconut oil and coconut milk. Objectives: This study aims to determine the effect of coconut flour substitution on the acceptability of noodles and the fiber content of substituted noodles. Methods: This study used a factorial design with Completely Randomized Design. The study was conducted with 30 untrained adult as panelists. Acceptability was measured by a preference test on 3 formulas consisting of a control formula without coconut flour substitution (F0), a substitution formula with a ratio of wheat flour to coconut flour 85%:15% (F1), a formula with a ratio of wheat flour to coconut flour 80% :20% (F2). Results: The substitution of wheat flour with coconut flour in noodles F1 and F2 percent increased the fiber composition in noodles from 1.99g/100g to 5.98g/100g and 7.31g/100g. Substitution did not have a significant effect on the parameters of taste and aroma, but it did affect the decrease in the panelists' preference for the parameters of the color and elasticity of the noodles. Conclusions: The conclusion obtained is that the substitution of coconut flour in noodles increases the fiber content in the substituted noodle formula and decreases the acceptability in terms of the elasticity and color of the substituted noodles. F1 formula appears to be the best formula, which has the highest acceptability among substitution formula